Linguistic and Translational Errors on Bilingual Public Signs in the Saudi Southern Region: A Linguistic Landscape Study - Ahmed Al-Sofi Bakr Bagash Mansour; Hazaea Abduljalil Nasr; Alfaifi Abdullah (Open Cultural Studies)
This study investigates the linguistic errors and mistranslation of bottom-up public signs (BUPSs) in a tourist area in the southern region of Saudi Arabia, namely Abha. It specifically aims to identify the types of linguistic errors and inaccurate translations found in the static BUPSs. It also examines the underlying causes behind these errors and proposes remedial strategies that could minimize them. A conceptual framework was developed based on linguistic landscape and interlanguage analysis. A qualitative research design was utilized, which involved ethnographic walks at the research site and semi-structured interviews with translators and linguists. Thematic analysis was employed to achieve the research objectives. The findings showed morphological, syntactical, semantic, pragmatic, and contextual/discourse-related errors. Furthermore, transliteration and inaccurate translation were widely used. These errors were primarily traced back to several factors, including machine translation, the incompetence of sign producers, carelessness among the signs’ producers and business owners, and a lack of awareness of cultural differences. Effective and remedial strategies were proposed for stakeholders to minimize these distractors, including hiring qualified translators and professional linguists, minimizing overreliance on machine translation, activating official regulations for sign production, and reviewing the signs before circulation. Further research is recommended on ideological and linguistic choices in tourist areas. This study adds pragmatic and discourse-related errors to the list of errors displayed on public signs.